How can a mobile service provider reduce costs with software‐defined networking?. (8th December 2015) - Naudts, Bram; Kind, Mario; Verbrugge, Sofie; Colle, Didier; Pickavet, Mario
Summary: Network architecture innovation has been driven by virtualization and centralization of network control based on software‐defined networking (SDN) and by network functions moved to the cloud with network function virtualization (NFV). These two principles are considered as promising enablers to reduce costs and spur innovation. In the first part of the paper, we argue that the evolved packet system (EPS) can be seen as a service function chain and an area in which service providers can capitalize on SDN and NFV capabilities. A multi‐layer modular architecture for carrier networks based on SDN and NFV principles is provided. In the second part of the paper, we focus solely on SDN, and we argue that service providers can benefit from SDN to reach cost savings in their mobile network. Our work focuses on the cost savings that can be reached via the centralization of control and the operational paradigm of developing and operating the network management software in‐house instead of buying a vendor solution only. We quantify the potential cost savings that can be reached in an Internet protocol/multi‐protocol label switching‐based transport service with SDN capabilities that interconnects the key functional elements in a mobile network. In the analysis, we evaluate the impact on capital expenditures and provide details on the impact on operational expenditures. The evaluation can serve as a blueprint for techno‐economic analysis of the mobile network operator's processes in the transport network of a mobile network. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This article proposes a multi‐layer modular architecture for carrier networks based on SDN and NFV principles and quantifies the potential cost savings that can be reached in an IP/MPLS‐based transport service with SDN capabilities that interconnects the key functional elements in a mobile network Our findings show savings of 12% which could be attributed to the lower expenditures on equipment for CapEx and lower expenditures for service provisioning and service management for OpEx.